Writing ethnohistory in the Philippines narrating and theorizing culture. [article]. - Rovillos, Raymundo D.
This paper explores the "poetics and politics" (Clifford and Marcus 1986) of writing etnohistory in the Philippines. This is achieved by scrutinizing selected ethnohistories from different ethnographic regions in the Philippines: Cordillera, Central and South Luzon, and Mindanao -(from the author)